Gradually truncated log-normal in USA publicly traded firm size distribution - Gupta, Hari M.; Campanha, Jose R.; de Agular, Daniela R.; Queiroz, Gabriel A.; Raheja, Charu G. (Elsevier B.V., 2007)
We study the statistical distribution of firm size for USA and Brazilian publicly traded firms through the Zipf plot technique. Sale size is used to measure firm size. The Brazilian firm size distribution is given by a log-normal distribution without any adjustable parameter. However, we also need to consider different parameters of log-normal distribution for the largest firms in the distribution, which are mostly foreign firms. The log-normal distribution has to be gradually truncated after a certain critical value for USA firms. Therefore, the original hypothesis of proportional effect proposed by Gibrat is valid with some modification for very large firms. We also consider the possible mechanisms behind this distribution. (c) 2006 Published by Elsevier B.V.
Keywords: firm size; gradually truncated log-normal; Gibrat theory